Malecón turístico de Girardot como estrategia de intervención del espacio público en la ronda del río Magdalena (2022)
Girardot, a municipality located in the southwestern department of Cundinamarca, historically identified as the main supplier of the area, starting with the first distributor port of the Magdalena River, one of the most important market places is located in this municipality declared a national heritage being a flagship in the food distribution network.